Building Ethics in Organizational Psychology Decision Making in Islamic Educational Institutions at Insan Cermat Elementary School - Ende Widiyana; Mulyawan Safwandy Nugraha (al-Afkar, Journal For Islamic Studies, 2025)
Islamic educational institutions have a great responsibility in building the ethics and personality of their students The challenge of Islamic education today is the emergence of a shift in ethical values and personality in society due to the influence of globalization, technological advances, social problems and disparities in different economic capabilities which indirectly lead to social conflicts, disharmonization of relationships between parents and children, teachers and students and so on. This research aims to develop ethics in the decision-making process in the field of organizational psychology, especially in the Islamic Education Institution SDIT Insan Cermat. This study examines the psychological factors that influence ethical decision-making by leaders and educators, including morality, intrinsic motivation, and perceptions of justice in the organization. Data were collected through interviews and observations. The findings show that the application of ethics in decision-making can strengthen organizational integrity, create a more conducive work atmosphere, and improve the overall performance of the institution.